SIFAT ORGANOLEPTIK DAGING KELELAWAR DENGAN WAKTU PEMASAKAN YANG BERBEDA - Ruba, Elisabeth; Ransaleleh, Tiltje Andretha; Rumondor, Delly B.J.; Palar, Conny K.M.; Rompis, John E.G. (ZOOTEC, 2018)
THE ORGANOLEPTIC PROPERTIES OF BAT MEAT WITH DIFFERENT COOKING TIMES. A study that aims to determine the level of consumer preferences in processed bat meat with different cooking time. This research was conducted from July 27 until August 31, 2017 at Animal Production Technology Laboratory Faculty of Animal Husbandry of Sam Ratulangi University of Manado . This study uses 3000 grams of bat meat. The experimental design used was Completely Randomized Design 4 treatments and 30 replications. Treatment arrangement as follows: R1 = 750 grams of bat meat cooked for 15 minutes; R2 = 750 grams of bat meat cooked for 30 minutes; R3 = 750 grams of bat meat cooked for 45 minutes; R4 = 750 grams of bat meat cooked for 60 minutes.The results showed that the level of favorite color, texture, tenderness and taste gives a real effect on the duration of cooking timebat. However, the level of aroma preferences does not affect the cooking time. Based on the research results can be concluded that the cooking time of bats meat for 60 minutes gives the nature of color, texture, aroma, tenderness and taste that can be accepted by consumers.Â Keywords: Bat meat, organoleptic, cooking time